2020
DOI: 10.1088/1742-6596/1575/1/012121
|View full text |Cite
|
Sign up to set email alerts
|

A Panoramic View System of Guilin Tourism Based on Interactive Projection Technology

Abstract: This paper introduces a panoramic view system of Guilin Tourism based on virtual reality and infrared image tracking. Users interact with images on the ground through body movements, the system can achieve unattended, interactive guided, automatic voice interpretation function, with virtualization, high efficiency, easy maintenance, good interactive experience and so on. Suitable for placing in exhibition venues, scenic spots exhibition hall and so on, so that tourists can enjoy Guilin landscape without leavin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The graphics engines or add-ons used to create XR application scenarios in all studies included in this analysis are shown in Table 7. [3,4,9,13,18,22,[24][25][26][27][28]32,36,53,59] Not specified…”
Section: Discussion Of Virtual Engines For Creating Xr Scenariosmentioning
confidence: 99%
See 3 more Smart Citations
“…The graphics engines or add-ons used to create XR application scenarios in all studies included in this analysis are shown in Table 7. [3,4,9,13,18,22,[24][25][26][27][28]32,36,53,59] Not specified…”
Section: Discussion Of Virtual Engines For Creating Xr Scenariosmentioning
confidence: 99%
“…Fully immersive experiences, panoramic roaming, virtual simulation. 56 [3][4][5][6][7][8][9][10][11][12][13][14][15][45][46][47][48][49][50]53,54,[58][59][60][61][62][63][66][67][68][69][70]82,83] AR Environment perception integration of virtual and real, enhanced interactive experience. 15 [16][17][18][19]21,39,46,51,52,54,57,61,63,64,69] MR Virtual and real seamless integration, multimode real-time interaction.…”
Section: Vrmentioning
confidence: 99%
See 2 more Smart Citations
“…When the user's body parts (such as hands and feet, or even the whole body) enter the projection area, the system tracks and captures the occluded area of the user's body through the infrared camera, and transmits the location data of the occluded area to the system. The tracking target position information is converted into control signal to realize the interactive action feedback of the control virtual reality screen [5].…”
Section: Types and Characteristics Of Digital Media Interaction Techn...mentioning
confidence: 99%